Additive manufacturing of metals : the technology, materials, design and production /: the technology, materials, design and production. (2017) - Yang, Li; Hsu, Keng; Baughman, Brian; Godfrey, Donald G; Medina, Francisco; Menon, Mamballykalathil; Wiener, Soeren
No abstract available